RUSSIAN AND CHINESE SYSTEMS OF DEVELOPMENT COOPERATION: A COMPARATIVE ANALYSIS - Degterev, D.A.; Yan, L.; Trusova, A.A. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Mezhdunarodnye otnosheni͡a, 2017)
The subject of this study are the mechanisms of development cooperation both in the Rus-sian Federation and China. The authors carry out a comparative analysis of the regulatory bases of the two states in the sphere of development cooperation, organizational structures, conceptual apparatus, specifics of Russian and Chinese foreign aid. The methodological basis of this research is based on the principles of reliability and scientific objectivity. In the study methods of comparative-comparative analysis are applied. Strategic partnership between the Russian Federation and the People’s Republic of China, including conjugation of the project of the Economic belt of the Silk Road and the Eurasian Economic Union, creates prerequisites for successful interaction of the two states in the field of international assistance to third countries. In the legislation of the PRC, there is a conceptual basis for official development assistance, it includes “White Books” and other political documents that establish the principles, goals and objectives, the mecha-nism for the implementation of China's external assistance. In the Russian Federation, there is a Concept of State Policy in the Sphere of International Development Assistance, which reflects the goals, objectives, principles for the implementation of development cooperation, but does not approve at the legislative level the mechanism for providing assistance. In both countries there is also no specialized government agency that would implement policies to promote development cooperation. It is rather a matter of a number of state bodies in the sphere of development cooperation, whose activities are to some extent coordinated on an interagency basis. The analysis of doctrinal and normative documents, as well as existing programs of development cooperation of the Russian Federation and the PRC, regional and sectoral priorities, makes it possible to develop recommendations on coordinating the efforts of the Russian Federation and the PRC in the field of promoting development cooperation, which will ultimately lead to an increase in the effectiveness of national programs of foreign aid.